Excitation Energy Transfer and Trapping in Higher Plant Photosystem II Complexes with Different Antenna Sizes - Caffarri, Stefano (The Biophysical Society, 2011)
We performed picosecond fluorescence measurements on well-defined Photosystem II (PSII) supercomplexes from Arabidopsis with largely varying antenna sizes. The average excited-state lifetime ranged from 109 ps for PSII core to 158 ps for the largest C(2)S(2)M(2) complex in 0.01% α-DM. Excitation energy transfer and trapping were investigated by coarse-grained modeling of the fluorescence kinetics. The results reveal a large drop in free energy upon charge separation (>700 cm(−1)) and a slow relaxation of the radical pair to an irreversible state (∼150 ps). Somewhat unexpectedly, we had to reduce the energy-transfer and charge-separation rates in complexes with decreasing size to obtain optimal fits. This strongly suggests that the antenna system is important for plant PSII integrity and functionality, which is supported by biochemical results. Furthermore, we used the coarse-grained model to investigate several aspects of PSII functioning. The excitation trapping time appears to be independent of the presence/absence of most of the individual contacts between light-harvesting complexes in PSII supercomplexes, demonstrating the robustness of the light-harvesting process. We conclude that the efficiency of the nonphotochemical quenching process is hardly dependent on the exact location of a quencher within the supercomplexes.